Estimated cost of transporting construction and demolition waste in Recife, Pernambuco, Brazil - Ferraz, Paulo Henrique Ribeiro (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The construction sector has grown significantly in the last decade, also expanding the environmental damage inherent to the activity, especially the production of solid waste, with an annual estimate of over 760,000 tons for the municipality of Recife. Proper disposal of construction and demolition waste (RCD) should be technically and economically feasible, where the collection and disposal process results in an additional cost for any building work, and transportation is a relevant stage of this, where its value is determined by variables such as distance, traffic and access road conditions. This study aims to analyze the variation in the cost of transportation of RCD in Recife, starting with a survey of the destination points on the CPRH page, delimiting three coverage areas, and calculating the minimum mean transport distances (DMT). and maximum in the demarcated regions, being observed the variations of the DMTs in each area, through the Tukey test. As a price reference, the SINAPI table was used, calculating the minimum and maximum costs for each area. Finally, a considerable variation in the minimum cost was observed in one of the areas, while no relevant disparities in the maximum price were detected.